Non-Democratic Regimes and Participation in UN Peacekeeping Operations. Issue 1 (1st January 2023) - Levin, Andrew
ABSTRACT: Do democratic or non-democratic countries contribute more personnel to UN peacekeeping operations? While earlier studies found that democracies make larger contributions than non-democracies, recent research has challenged these findings. Scholarship in this area, however, has largely conceived of 'non-democracy' as a monolithic category, despite a growing body of research delineating distinct types of illiberal regimes and identifying their divergent behaviours in a range of domestic and international contexts. In this article, I argue that non-democracies' personnel contributions to peacekeeping operations vary based on different 'type' of illiberal regime, and that this variation is contingent on two main factors: the influence of the military within the regime, and the extent to which a regime values the prestige associated with large-scale peacekeeping contributions. I test this proposition by statistically analyzing data from UN peacekeeping operations between 1991–2018. The findings indicate that single-party regimes are likely to make significantly smaller contributions than democracies; the contribution behaviour of other types of non-democracies is less discernible from their democratic counterparts.